Impact of Food Allergies on the Food Safety and Life Quality of Adults in Spain - Eulalia Antich Ferrer; Sandra Fernández-Pastor; Ana Guerrero (Foods)
Food allergies are increasingly frequent immune system reactions triggered by allergens present in food, which can affect quality of life. To investigate the impact of food allergies among Spanish adults and the influence of gender and age of diagnosis, an online survey using the shortened version of the Adult Food Allergy Quality of Life Questionnaire (FAQLQ) was conducted. A total of 134 participants with food allergies were enrolled in the exploratory study. Significant differences (p ≤ 0.050) were found in the perception of the emotional and social impact of food allergies on quality of life. Age of diagnosis (childhood, adolescence, or adulthood) had a greater influence on more variables than gender. Men reported greater fear of accidentally consuming something that could trigger an allergic reaction compared to women (p = 0.003), while women felt more excluded due to their allergies (p = 0.030). Overall, the perception of eating out was characterized by insecurity. The quality of life of individuals with food allergies could be improved through the use of pictograms on labels, menus, and increased training in the foodservice industry regarding allergens. Multiple additional investigations are recommended to generalize current findings.